2021
DOI: 10.1186/s13018-021-02837-0
|View full text |Cite
|
Sign up to set email alerts
|

In adults, early mobilization may be beneficial for distal radius fractures treated with open reduction and internal fixation: a systematic review and meta-analysis

Abstract: Objectives It remains debatable if early mobilization (EM) yields a better clinical outcome than the late mobilization (LM) in adults with an acute and displaced distal radial fracture (DRF) of open reduction internal fixation (ORIF). Therefore, we aimed to perform a systematic review and meta-analysis of randomized controlled trials (RCTs), comparing clinical results with the safety of EM with LM following ORIF. Methods Databases such as Medline, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 45 publications
0
3
0
1
Order By: Relevance
“…reported that early mobility reduced hospitalization by an average of 1.8 days in total joint arthroplasty [ 96 ], and Deng et al. reported that patient‐reported outcome measures (PROMs) score of the early mobilization group was significantly better than that of the late mobilization group after distal radius fracture surgery [ 97 ].…”
Section: Components Of Eras Protocolmentioning
confidence: 99%
“…reported that early mobility reduced hospitalization by an average of 1.8 days in total joint arthroplasty [ 96 ], and Deng et al. reported that patient‐reported outcome measures (PROMs) score of the early mobilization group was significantly better than that of the late mobilization group after distal radius fracture surgery [ 97 ].…”
Section: Components Of Eras Protocolmentioning
confidence: 99%
“…The entire device sits medially along the radial side of the wrist. The hinge allows for early wrist joint mobility, which may improve functional outcomes [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, our conclusion that surgery does not provide additional benefits is unlikely to change in people over 70 based on blinded trials. Moreover, blinding may not be feasible, as the surgical group would lose the benefit of early mobilization in a placebo-controlled trial (Deng et al., 2021).…”
Section: Discussionmentioning
confidence: 99%